1995
DOI: 10.2190/yb6q-hx39-11kk-gkyl
|View full text |Cite
|
Sign up to set email alerts
|

Course Structure Effects on Students' Computer Anxiety, Confidence and Attitudes

Abstract: This study investigated the effects of course structure variables on the computer anxiety, confidence, and attitudes of pre- and in-service teachers. These course structure variables included the number of weeks the course met (course length) and the number of meetings per week (course frequency). Differences in course structure had significant effects on changes in the students' computer anxiety, confidence, liking, and perceptions of usefulness. With equivalent number of course hours, students in courses tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Organizations should therefore provide adequate resources, such as training. In addition, giving new users more time (to reduce pressure) and more attention from supervisors may reduce anxiety in a cost-effective way [41].…”
Section: Discussionmentioning
confidence: 99%
“…Organizations should therefore provide adequate resources, such as training. In addition, giving new users more time (to reduce pressure) and more attention from supervisors may reduce anxiety in a cost-effective way [41].…”
Section: Discussionmentioning
confidence: 99%
“…According to Anastasi, studies of face-to-face courses suggest that, contrary to previous research, students tend to perform as well in abbreviated courses, and the belief that shortened courses are somehow inferior to full-semester courses is unfounded. Earlier research by Bohlin and Hunt (1995) found that student attitudes in a face-to-face traditional format course were more positive than student attitudes in an intensive shortened face-to-face format.…”
Section: Introductionmentioning
confidence: 94%
“…This supported the finding by Bohlin and Hunt (1995) that computer experience spread over time is more effective in reducing computer anxiety than an intensive short experience. Harris and Grandgenett (1996) looked at the impact anxieties and demographics had on telecomputing activity of educators.…”
Section: Research Oa Computer Anxietysupporting
confidence: 84%
“…Both found that computer experience reduced computer anxiety. While the studies by Bohlin and Hunt (1995) and Ayersman and Reed (1996) focused on other variables, their findings also indicated that increased experience with computers reduced anxiety. The research indicated that almost any computer experience reduced computer anxiety.…”
Section: Computer Anxiety Summarymentioning
confidence: 97%
See 1 more Smart Citation